A child with melioidosis presenting as septic arthritis - Sontichai, Watchareewan; Oberdorfer, Penninah (Biomedical Sciences and Clinical Medicine, 2016)
Melioidosis has various clinical and rheumatological manifestations that may be the fi rst presentation. This disease is less common in children than adults. This study reports the case of a previously healthy 3-year-old boy who presented with high-grade fever and pain in the right hip. He was treated with empirical parenteral antibiotics for septic arthritis and arthrotomy, but his symptoms did not improve. A hemoculture and synovial fl uid culture had no bacterial growth. A titer of indirect hemagglutination assay for melioidosis was 1:2048, which is strongly positive. Melioidosis was diagnosed. Intravenous ceftazidime was given for 14 days as intensive treatment before switching to eradication therapy with oral trimethoprim and sulfamethoxazole for 3 months. A 3-phase bone scan also revealed osteomyelitis of the right tibia. The patient gradually improved and was discharged.